Pengaruh Pemberian Kalium Yodida terhadap Pertambahan Bobot Badan dan Berat Karkas Kambing Peranakan Etawah Jantan Lepas Sapih - Widjaya, Nilawati (Fakultas Peternakan Universitas Jambi, 2011)
The research was conducted to study the effect of Kalium Iodide (KI) Â to body weight gain and carcass weight ofÂ male after-weaned Peranakan Etawah (PE) goat. Nine head of goat allotted into three treatment :P0 (control), P1 (administration of 0.1 ml KI), and P2 (administration of 0.2 ml KI). The KI was injected subcutaneously twice a week. Data was analyzed by GLM procedure using SPSS. In conclusion, KI administration subcutaneously injected twice a week increased daily gain and carcass weight of post weaning male PE goat.